Teaching with integrated digital tools and Artificial Intelligence in the History Program at the Pontifical Catholic University of Peru - Lossio Chávez, Jorge (2024)
This article analyzes the outcomes of a teaching innovation project that integrated digital tools and artificial intelligence into history courses at a private university in Peru (the Pontifical Catholic University of Peru) during 2023 and 2024. The teaching innovation demonstrated that these technologies transform the classroom experience by generating new research questions, enabling the analysis of complex social processes, and approaching data collection and the dissemination of student research in new ways. The interactivity of digital tools promotes an interdisciplinary approach and greater student participation in the classroom, preparing students for the professional challenges of the 21st century.